UNDERSTANDING THE 4+2 ENGLISH LANGUAGE APPROACH: A PERSONAL REFLECTION ON MY INTERNSHIP (Ustozlar uchun, 2025)
This article explores the 4+2 English Language Program and reflects on my personal experiences during the school internship. The 4+2 program offers a unique approach to learning, integrating both theoretical and practical aspects of the English language. Throughout my internship, I was able to observe and participate in various teaching methods, gaining insight into the challenges and rewards of teaching English in a real classroom setting. This paper highlights key experiences, challenges, and the impact of the 4+2 curriculum on my development as a future educator, emphasizing its practical relevance and educational value.